Diagnostic Accuracy of the White Side Test and Assessment of Oxidative Stress Biomarkers in Cows with Subclinical Endometritis - Singh, Pawan Preet; Malik, Asloob Ahmad; Sofi, Khursheed Ahamd; Naikoo, Mehrajuddin; Pampori, Zahoor Ahmad; Hassan, Mir Nadeem; Shah, Syed Mohmad (Indian Journal of Veterinary Sciences and Biotechnology, 2026)
Subclinical endometritis (SCE) in dairy cattle negatively impacts fertility and poses a significant diagnostic challenge in bovine practice. The current study was conducted based on the hypothesis that SCE in cows alters the serum concentrations of nitric oxide (NO) and lipid peroxides (LPO). The study was carried out across different districts of the Kashmir Valley. A total of 54 cows that had calved at least once and were more than 60 days in milk (DIM) at the time of estrus were included. Initial screening was performed by endometrial cytology using cytobrush technique as reference method (polymorphonuclear cells ≥4%). Out of 54 animals screened, 41 cows were found positive for SCE, while 13 were negative. The sensitivity and specificity of White side test based on ROC curve was 78% and 53.8%, respectively, in comparison to endometrial cytology at optimal cut-off point ≥0.5 (mild infection). Cows diagnosed with SCE at estrus showed significantly (p
Keywords: Cytobrush; Dairy cows; MDA; Nitric oxide; Subclinical endometritis; White side test